The Life of Benjamin Franklin, vol. I: Journalist, 1706-1730/The Life of Benjamin Franklin, vol. II: Printer and Publisher, 1730-1747. - Walters, Kerry S. (Journal of American History, 2006)
The article reviews the two volumes "The Life of Benjamin Franklin, vol. I: Journalist, 1706-1730/The Life of Benjamin Franklin, vol. II: Printer and Publisher, 1730-1747" by J. A. Leo Lemay.